Application of multilayer ceramic filter elements for purification of industrial water in foundry production - S. M. Azarov; O. V. Chernevich; S. V. Shemchenok (Литьë и металлургия)
On the basis of multilayer filter elements of mineral raw material of the Republic of Belarus an installation for purification of industrial water in foundry production has been worked out.